Low bone turnover and reduced angiogenesis in streptozotocin-induced osteoporotic mice. (3rd July 2016) - Peng, Jia; Hui, Kang; Hao, Chen; Peng, Zhao; Gao, Qian Xing; Jin, Qi; Lei, Guo; Min, Jiang; Qi, Zhou; Bo, Chen; Dong, Qian Nian; Bing, Zhou Han; et al.
ABSTRACT: It is known that type 1 diabetes (T1D) reduces bone mass and increases the risk for fragility fractures, an effect that has been largely ascribed to decreased bone formation. However, the potential role of decreased angiogenesis as a factor in osteogenesis reduction has not been extensively studied. Furthermore, there is controversy surrounding the effect of T1D on bone resorption. This study characterized bone microstructure, bone strength, and bone turnover of streptozotocin (STZ)-induced diabetic mice (T1D mice) and explored the role of angiogenesis in the pathogenesis of T1D-induced osteoporosis. Results demonstrate that T1D deteriorated trabecular microarchitecture and led to reduced bone strength. Furthermore, T1D mice showed reduced osteoblast number/bone surface (N.Ob/BS), mineral apposition rate, mineral surface/BS, and bone formation rate/BS, suggesting attenuated bone formation. Decreased angiogenesis was shown by a reduced number of blood vessels in the femur and decreased expression of platelet endothelial cell adhesion molecule (CD31), nerve growth factor, hypoxia-inducible factor-1α, and vascular endothelial growth factor was observed. On the other hand, reduced bone resorption, an effect that could lead to impaired osteogenesis, was demonstrated by lower osteoclast number/BS and decreased tartrate-resistant acid phosphatase and cathepsin K mRNA levels. Reduced number of osteoblasts and decreased expression of receptor activator for nuclear factor-κB ligand could be responsible for compromised bone resorption in T1D mice. In conclusion, T1D mice display reduced bone formation and bone resorption, suggesting decreased bone turnover. Furthermore, this study points to impairments in angiogenesis as a pivotal cause of decreased bone formation.